Diagnosis and Social Justice Advocacy: Reconciling Tensions for Students and School Counsellors - Kennedy, Lindsay J. (Canadian Journal of Counselling and Psychotherapy, 2016)
Combining the existing diagnostic system with social justice advocacy creates tensions for school counsellors and their clients. A central tension is that diagnoses enable individual-level social justice advocacy by allowing students and their families to access mental health services, while constraining systemic change related to the dominance of the diagnostic system. Suggestions are offered about how tensions can be reconciled to facilitate, rather than constrain, the mental health services offered in Kindergarten to Grade 12 schools. In highlighting tensions and possibilities, an integrative both/and perspective emerges that respects the utility of the discourse of diagnosis and social justice advocacy.